HRM models of online labor platforms: Strategies of market and corporate logics - Immonen, Jere (Frontiers in Sociology, 2023)
Studies on online labor platforms (OLPs) have revealed that OLPs can have extensive managerial control over independent workers which affects workers’ autonomy and precariousness. The permeability of the control makes some OLPs' roles as neutral intermediates of labor exchanges questionable. While there are several platform work studies on the effects of human resource management (HRM) activities, earlier studies have focused more on certain type OLP companies and have not managed to bring out the variations of HRM activities in different OLPs. Earlier OLP classifications have not made systematic distinctions between HRM activities either. This paper offers a classification to view how HRM activities can be manifested in OLPs. The study uses an idea of institutional complexity and claims that OLPs balance their operations between complexity of two institutional logics, market, and corporation, by using varying strategies with their HRM activities. Differently managed OLPs are also often marketed to different workers groups. This indicates that workers’ levels of autonomy differ between OLPs. Hence, platform workers’ expectations towards OLPs, perceptions of fairness and experiences of well-being may also be influenced by the HRM activities, in which they operate. The study utilizes terms of services and webpage data of 46 multinational and Finland-based OLPs. Based on this data, OLPs have been classified into six models by five governance principles and institutional logics. The results provide contribution to the ongoing discussions of power asymmetries between OLPs and platform workers, and thus OLPs’ roles more as either marketplaces or hierarchical corporations. Formed models can be utilized to deepen studies on key issues of platform workers autonomy, precariousness, and experiences in different types of OLPs.